Supporting families experiencing homelessness : current practices and future directions - Perlman, Staci; Cowan, Beryl Ann; Haskett, Mary E. (Springer New York, 2014)
"This book is an extremely welcome addition to the literature on homelessness, and the only one solely devoted to the needs of families and children. This timely volume is a creative compendium of chapters that explores every aspect of the issue and describes the cutting edge of the field." - From the foreword, Ellen L. Bassuk, M.D., National Center on Family Homelessness, Center for Social Innovation, and Harvard Medical School With more American families being increasingly forced into homelessness, Supporting Families Experiencing Homelessness aims to raise the standard and scope of services provided to families without homes through practices that are both strengths-based and culturally competent. All major aspects of this important topic are analyzed, with recommendations for what is needed to improve current programs or establish new ones. Chapters set out the particular needs of parents, children, and teens as well as homeless subpopulations, such as youth who age out of foster care. This book presents a real-world framework for services that are client-centered, are integrated across provider systems, and follow families in their transition to stable housing. Included in this volume: The ecology of family homelessness. Developmental and mental health outcomes of sheltered infants, children, and adolescents. Parenting in the face of homelessness. Trauma-informed practices in shelters and other programs serving homeless families. Cultural competence and individualized care in service provision. Evidence-based and promising approaches to service provision and intervention. A groundbreaking volume, this book is a must-read for students preparing for careers in human services, all frontline providers working with those at-risk for housing instability or currently living without homes, and researchers and policy-makers working to enhance outcomes for families experiencing homelessness.